please help . tjjhhhhhhhh
![please help tjjhhhhhhhh class=](https://us-static.z-dn.net/files/d6d/95463ea449df4ddc473f012ae822d54a.jpg)
Answer:
19 - 8√3
Step-by-step explanation:
(-4 + √2)^2
= (-4)^2 + 2(-4)(√3) + √3)^2
= 16 - 8√3 + 3
= 19 - 8√3
Answer:
D
Step-by-step explanation:
note that ([tex]\sqrt{3}[/tex] )² = 3
Given
(- 4 + [tex]\sqrt{3}[/tex] )² = (- 4 + [tex]\sqrt{3}[/tex])(- 4 + [tex]\sqrt{3}[/tex])
Expand using (a + b)² = a² + 2ab + b²
= (- 4 )² + 2(- 4[tex]\sqrt{3}[/tex] ) + ( [tex]\sqrt{3}[/tex] )²
= 16 - 8[tex]\sqrt{3}[/tex] + 3
= 19 - 8[tex]\sqrt{3}[/tex]